Soil resource inventory of the main campus Kerala Agricultural University Vellanikkara: Part II (WEST) - Sajnanth K (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2000)
Kerala Agricultural University is situated in Madakkathara panchayat in Thrissur district. It is having an area of about 380 ha in its main campus in Vellanikkara. The main campus includes three colleges and the areas of three Research Stations. In this campus, so many research works are going on in different fields. Thus the knowledge about the resource capacity may help in the production scenario of the University itself. In this ~ inventory, the western part of the. main campus, which includes the areas of Research stations and Farms .occupied mostly by perennial crops. For identification of sample sites, a 1 :2000 scale map of the campus was used.' A grid size of 80 m x 80m was used to locate the sites. ThF study area constitutes 12 blocks out of 37 in the campus. The samples were taken ~rom both surface (0-20cm). and subsurface (20-40cm) layer. Altogether 518 soil samples, collected from the 23 phases of the study area, were analysed by standard procedures to record their physical, chemical arid electrochemical properties. The surface and subsurface samples were analysed for available nutrients and other fertility parameters. The soils are gravelly in nature in surface and subsurface samples. Still an increase in amount of fine earth from surface to subsurface level was noted. The particle size analysis of the soil samples revealed that most of the samples were sandy clay loam in nature. In most of the soils, the texture was same for surface and subsurface samples. The data obtained on the soil components were used for their textural classificatio~. The most of the soil samples were acidic in nature. The electrical conductivity of almost all the samples was found to be very low in every phase. Buffer pH and hence the lime I requirement of the sa~ples has a very wide range among the soil phases. The organic carbon contents were medium in most of the soil samples. It is high in surface layer than subsurface in majority of the phases. Available phosphorus was generally low in content in 60 - 90% of samples. About 25% were in medium class. The potassium content was rated as low in 56% of the surface samples and 66% of subsurface samples.